Exploring Interactions in YouTube to Support the Identification of Crime Suspects - Florentino, Érick da Silva; Goldschmidt, Ronaldo Ribeiro; Cavalcanti, Maria Cláudia Reis (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
The identification of crime suspects on social networks (e.g. pedophilia, terrorism, etc.) has been one of the most relevant topics in social network analysis. The vast majority of methods are based on the extraction of textual content, senders and receivers from the network, but do not take into account the interactions that occur inside the textual content. The present work raises the hypothesis that these interactions, if taken into consideration, can lead to better results when it comes to identifying crime suspects. To validate this hypothesis, an algorithm named TROY was developed to define and represent the interactions that occur in Youtube. Then, it is proposed as the first stage of the INSPECTION method, which analyzes the textual content exchanged on a social network, in order to identify crime suspects. This method is based on the use of a controlled vocabulary with terms categorized according to a certain domain (for example, pedophilia, cyberbullying, terrorism, etc.). Experiments on the pedophilia domain were carried out applying the INSPECTION method to Youtube. The first stage of the method may use any algorithm that is able to extract social interactions. In this case, we used TROY and another algorithm called CRAWLER, which does not take into account the previously mentioned interactions. The results showed that the TROY algorithm obtained better results than the CRAWLER algorithm, validating the hypothesis raised.